Optimization of Phenolic Compounds Extraction from Aerial Parts of Fabiana punensis S. C. Arroyo by Ultrasound- and Microwave-Assisted Extraction - Gonzalez, Daniela Alejandra (2024)
Fabiana punensis S. C. Arroyo is a subshrub or shrub that is indigenous to the arid and semiarid region of northern Argentina and is known to possess several medicinal properties. The objective of this study was to optimize the extraction conditions so as to maximize the yield of bioactive total phenolic compound (TPC) and flavonoids (F) of F. punensis’ aerial parts by using nonconventional extraction methods, namely ultrasound-assisted extraction, UAE, and microwave-assisted extraction, MAE, and to compare the biological activities and toxicity of optimized extracts vs. conventional extracts, i.e., those gained by maceration. Response Surface Methodology (RSM) was used to apply factorial designs to optimize the parameters of extraction: solid-to-liquid ratio, extraction time, ultrasound amplitude, and microwave power. The experimental values for TPC and F and antioxidant activity under the optimal extraction conditions were not significantly different from the predicted values, demonstrating the accuracy of the mathematical models. Similar HPLCDAD patterns were found between conventional and UAE- and MAE-optimized extracts. The main constituents of the extracts correspond to phenolic compounds (flavonoids and phenolic acids) and apigenin was identified. All extracts showed high scavenger capacity on ABTS•+, O2 •− and H2O2, enabling the inhibition of the pro-inflammatory enzymes xanthine oxidase (XO) and lipoxygenase (LOX). They also showed an antimutagenic effect in Salmonella Typhimurium assay and cytotoxic/anti-proliferative activity on human melanoma cells (SKMEL-28). Toxicological evaluation indicates its safety. The results of this work are important in the development of efficient and sustainable methods for obtaining bioactive compounds from F. punensis for the prevention of chronic degenerative diseases associated with oxidative stress, inflammation, and DNA damage.